2020
DOI: 10.1200/jco.2020.38.15_suppl.e16081
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics and outcomes of colorectal cancer (CRC) at Butaro Cancer Center of Excellence (BCCOE): Results from a retrospective cohort.

Abstract: e16081 Background: There are few studies on CRC in sub-Saharan Africa. BCCOE in Rwanda provides patients with CRC access to chemotherapy, surgery and radiotherapy referrals. Here, we describe patient characteristics, treatments delivered and outcomes. Methods: This retrospective observational study included 136 patients with CRC who presented between July 2012 and June 2018. We abstracted patient characteristics, diagnostic and treatment data, and outcomes from electronic and paper records. We compared baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
3
5
1
Order By: Relevance
“…In contrast to global data where CRC is reported to be more common in males than in females [9], in this study, we found that CRC was more common in females than in males (i.e., 63.0% versus 37.0%). Our findings also report a higher rate of female incidence than the 52.5% reported by Uwamariya et al [18] and the 52.2% reported by Fadelu et al [19].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In contrast to global data where CRC is reported to be more common in males than in females [9], in this study, we found that CRC was more common in females than in males (i.e., 63.0% versus 37.0%). Our findings also report a higher rate of female incidence than the 52.5% reported by Uwamariya et al [18] and the 52.2% reported by Fadelu et al [19].…”
Section: Discussionsupporting
confidence: 70%
“…CRC is underinvestigated in the Rwandan population. To our knowledge, only two papers [18,53] and one abstract [19] reporting on CRC in Rwanda have been published in international peer-reviewed journals within the last 10 years. In contrast to global data where CRC is reported to be more common in males than in females [9], in this study, we found that CRC was more common in females than in males (i.e., 63.0% versus 37.0%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 74 patients, we found that the mean age at diagnosis was 54.6 years with a wide age range between 22 and 81. This finding is similar to previous findings at the BCCOE and Kigali University Teaching Hospital (KUTH) with reported mean age at presentation of 52.5 and 54.3 years, respectively [ 24 , 25 ]. The mean age of males at diagnosis was 56.6 years and the mean age of females at diagnosis was 51.4 years.…”
Section: Discussionsupporting
confidence: 91%
“…The finding of a smaller proportion of CRC cases in patients under 40 years old at KFH (13.5%) as compared to previous studies in SSA corresponds with the population served by KFH. KFH is a private hospital and therefore tends to serve a patient population of a higher socioeconomic status, in contrast to some other hospitals providing cancer care in Rwanda such as BCCOE, where 58.1% of CRC patients lived in rural areas [ 25 ]. KFH patients primarily live in Kigali, an urban setting, and may have more access to lifestyles and diets associated with westernisation and therefore more exposure to risk factors that lead to higher incidences of CRC in countries like the USA.…”
Section: Discussionmentioning
confidence: 99%